El Aprendizaje como acontecimiento ético sobre las formas del aprender. Un Acercamiento a la Obra de Fernando Bárcena Orbe - Miranda Corzo, María Claudia (Universidad Santiago de Cali, 2017)
In this article the idea of the learning of Fernando Bárcena is resumed in a breakthrough of concepts ranging from the macro to the micro. In them re-lates the macro positions tradition and time to reach the reality of learning. It relates the fact of learning over time, with a past, a present and a future and re-veals that for the learning to take place there must be an ethical event because it allows the encounter with an "other". It develops reflections on learning by chance, learning of civility, learning as deception and as a relationship. Finally establishes a beautiful analogy between reading and learning. In this sense, learning is conceived as an event that changes the essence of existence, an event where experiences break the continuity that immobilizes and prevents the emergence of the free and thinking human being.